Genotypes of pathogenic Leptospira spp isolated from rodents in Argentina - Sylvia Grune Loffler; Maria Elisa Pavan; Bibiana Vanasco; Luis Samartino; Olga Suarez; Carmelo Auteri; Graciela Romero; Bibiana Brihuega (Memorias do Instituto Oswaldo Cruz, 2014)
Leptospirosis is the most widespread zoonosis in the world and significant efforts have been made to determine and classify pathogenic Leptospira strains. This zoonosis is maintained in nature through chronic renal infections of carrier animals, with rodents and other small mammals serving as the most important reservoirs. Additionally, domestic animals, such as livestock and dogs, are significant sources of human infection. In this study, a multiple-locus variable-number tandem repeat analysis (MLVA) was applied to genotype 22 pathogenic Leptospira strains isolated from urban and periurban rodent populations from different regions of Argentina. Three MLVA profiles were identified in strains belonging to the species Leptospira interrogans (serovars Icterohaemorrhagiae and Canicola); one profile was observed in serovar Icterohaemorrhagiae and two MLVA profiles were observed in isolates of serovars Canicola and Portlandvere. All strains belonging to Leptospira borgpetersenii serovar Castellonis exhibited the same MLVA profile. Four different genotypes were isolated from urban populations of rodents, including both mice and rats and two different genotypes were isolated from periurban populations.